A NEEDS ASSESSMENT FOR SOCIAL WORK INTERVENTIONS FOR CHILDREN AFFECTED BY HIV AND AIDS - Lukelelo, Nomvuyo; Roman, Nicolette; Schenck, Catherina (Social Work/Maatskaplike Werk, 2023)
Children are often left orphaned and without adult supervision when the parent or caregiver dies from HIV and AIDS-related illnesses. There is very little information available in South Africa on the type of interventions to reinforce the care and support provided to children affected by HIV and AIDS (CABHA). This study aimed to explore existing interventions provided to CABHA and the experiences of social workers in implementing interventions. Findings indicate that interventions are a continuous and collaborative process between social workers and stakeholders. A proper needs assessment should be done before implementing interventions to ensure that they benefit the children identified as needing intervention. Community-based interventions should not be underestimated as a significant source of support for CABHA.